MYC-driven epigenetic reprogramming favors the onset of tumorigenesis by inducing a stem cell-like state - Vittoria Poli (Nature Portfolio, 2018)
Breast cancer tumors originating from mammary luminal epithelial cells are highly heterogeneous. Here, the authors show MYC-driven tumor initiation is reliant on cell reprogramming via an epigenetic program which leads to mammary luminal epithelial cells acquiring basal/stem cell-like properties.